Boosting beauty in an economic decline mating, spending, and the lipstick effect. [article]. - Hill, Sarah
Although consumer spending typically declines in economic recessions, some observers have noted that recessions appear to increase women's spending on beauty products-the so-called lipstick effect. Uisng both historical spending data and rigorous experiments, the authors examine how and why economic recessions influence women's consumer behavior. Findings revealed that recessionary cues-whether naturally occurring or experimentally primed-decreased desire for most products (e.g. electronics, household items). However, these cues consistently increased women's desire for products that increase attractiveness to mates-the first experimental demonstration of the lipstick effect. Additional studies show that this effect is driver by women's desire for beauty products, this research provides novel insights into women's mating psychology, consumer behavior, and the relationship between the two. -(from the authors)